2015
DOI: 10.1159/000442199
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Cultural Adaptation of the Arabic Version of the Eating Assessment Tool (EAT-10)

Abstract: Background and Objectives: The Eating Assessment Tool (EAT-10) is a 10-item self-administered questionnaire. It is a noninvasive tool to measure patients' perception of their swallowing problems. The purposes of the present study were to develop an Arabic version of the EAT-10 and to evaluate its validity, consistency, and reliability in the Arabic-speaking population with oropharyngeal dysphagia. Setting and Design: This was a prospective study carried out at the Communication and Swallowing Disorders Unit, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 34 publications
5
44
0
3
Order By: Relevance
“…An A-EAT-10 score of ≥3 was considered to be indicative of abnormal swallowing based on the original work of Belafsky et al [5]. However, 2 other EAT-10 values have been reported in the literature [2, 6]. Rofes et al [6] suggested that reducing the cutoff value from 3 to 2 increased the test’s sensitivity by 5% without affecting specificity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An A-EAT-10 score of ≥3 was considered to be indicative of abnormal swallowing based on the original work of Belafsky et al [5]. However, 2 other EAT-10 values have been reported in the literature [2, 6]. Rofes et al [6] suggested that reducing the cutoff value from 3 to 2 increased the test’s sensitivity by 5% without affecting specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Rofes et al [6] suggested that reducing the cutoff value from 3 to 2 increased the test’s sensitivity by 5% without affecting specificity. Alternatively, Farahat and Mosallem [2] gave a mean score of 5.8 for dysphagia symptoms in a control group of 83 asymptomatic individuals in their validation of the A-EAT-10. The authors of the present study chose to abide by the cutoff value of Belafsky et al [5] in order to avoid false-negative or false-positive results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many of these screening questionnaires exhibit high internal consistency and test-retest reliability, the EAT-10 has gained the most widespread popularity due to its ease of use both in administering and scoring the questionnaire. This is evidenced by the translation and validation of the EAT-10 into Spanish [17], Portuguese (Brazilian and European) [18, 19], Italian [20], Arabic [21], Turkish [22], and Swedish [23]. …”
Section: Introductionmentioning
confidence: 99%
“…• Eating Assessment Tool (EAT-10) is a tool used to measure the swallowing problems. It is also validated in the Arabic language by Farahat and Mosallem [7] and called the validated Arabic version of Eating Assessment Tool (A-EAT-10) for Arab speaking patients with oropharyngeal dysphagia [7] .…”
Section: Introductionmentioning
confidence: 99%